Determinants of Neonatal Mortality in Kenya: Evidence from the Kenya Demographic and Health Survey 2014 - Akinyi Imbo; Elizabeth Mbuthia; Douglas Ngotho (International Journal of Maternal and Child Health and AIDS, 2021)
Background: Globally, there has been a marked decline in neonatal mortality and overall child mortality indicators from 1990 to date. In Kenya, neonatal deaths remain unacceptably high, contributing to 40% of under-five mortality rates (U5MR) making it an important health priority. The objective of this study was to identify the determinants of neonatal mortality in Kenya. An understanding of the determinants of neonatal mortality will provide evidence for better interventions to reduce these deaths.